FUTURE INNOVATION TRENDS IN LATIN AMERICA - T. V. Pospelova (Модернизация, инновация, развитие)
This article off ers an analysis of innovation activities in three Latin American countries. Such components as the role of science, business communities, and public policies in the transition to a knowledge-based economy are analyzed. Based on the Gibbons Model, innovative models that are being implemented inBrazil,Chile, andMexicoare compared. The data obtained may be used as a practical tool in developing countries.